2011
DOI: 10.4061/2011/943495
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rates in Open Fractures of the Tibia: Is the 6-Hour Rule Fact or Fiction?

Abstract: Aims. Emergency debridement has long been the standard of care for open fractures of the tibia as infection is an important complication. The timing of operative debridement can be debated. We review open fractures of the tibia and compare infection rates in those that were operated on within and after 6-hours. Method. 103 consecutive open fractures of the tibia were reviewed. The data was analysed retrospectively with regard to severity of fracture and incidence of infection. Infection rates over a three-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 10 publications
4
27
0
4
Order By: Relevance
“…36 However, the traditional 'six hour rule' has been challenged in recent literature. 11,37 Originally described by Friedrich in 1898, multiple studies have shown that this narrow time window should not be followed rigidly. 38,39 In our local hospitals, the demand for emergency theatre time does not permit surgery in the first six hours due to the high trauma burden and relative staff shortages.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, the traditional 'six hour rule' has been challenged in recent literature. 11,37 Originally described by Friedrich in 1898, multiple studies have shown that this narrow time window should not be followed rigidly. 38,39 In our local hospitals, the demand for emergency theatre time does not permit surgery in the first six hours due to the high trauma burden and relative staff shortages.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies showed that there is no significant statistical difference between open fractures operated before or after the 6 th hour time and the occurrence of infection [14] [17]- [19]. Surgeon's experience plays no role on the occurrence of an infection after nailing.…”
Section: Resultsmentioning
confidence: 99%
“…Variation of rates could be explained by timing of surgery, and more imprtantly the regularity of antibiotherapy and working conditions [15] [19]. It is important that patients meet the cost of their antibiotics from admission to healing.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…Kamat et al [21] found an infection rate of 11.6 %, Singh et al [22] found 14.9 %, and Spencer et al [9] showed 14.6 % cases of infection. These reports slightly differ from the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…These reports slightly differ from the present paper. In the study by Kamat et al [21] there were only 21.3 % of Gustilo type III fractures and all the cases were operated within a period of less than 17 h, 93 % of the Gustilo type III patients (49.5 %) in the study by Spencer et al [9] were treated within 12 h of the injury, and 69 % of the type III fractures were treated within 6 h in the report by Singh et al [22]. …”
Section: Discussionmentioning
confidence: 99%